Hormonal differences in perpetrators of intimate partner violence - Cantos, Arthur L.; Ontiveros, Gabriela; Dearth, Robert K.; O’Leary, K. Daniel (Frontiers in Psychiatry, 2024)
Objective: In order to gain a better understanding of the individual and joint impact of testosterone and cortisol on behavior, the present study was developed to test the differences in each hormone alone and conjointly between perpetrators of IPV and non-violent controls.Method: Perpetrators of IPV on probation were compared to a control group of non-aggressive males from Hidalgo County in the Rio Grande Valley on baseline testosterone and cortisol, as well as several relevant questionnaires measuring aggression and trait anger. Differences in cortisol following exposure to a stressful event were also examined. Procedures included two laboratory visits consisting of questionnaires, a number of salivary testosterone and cortisol collections, and exposure to a stressor.Results: Perpetrators had higher basal testosterone and post stressor cortisol levels than nonviolent controls as well as a higher T/C ratio. In addition, trait anger moderated the relationship between both testosterone alone, and the testosterone/cortisol ratio and perpetration of IPV.Conclusion: Results are consistent with the hypothesis that testosterone leads to antisocial behavior, including perpetration of violence. The results are also consistent with the dual hormone hypothesis, i.e., that testosterone and cortisol work together to jointly regulate social dominance and aggression. Both the increased freestanding testosterone and the increased cortisol following exposure to stress places these men at risk for perpetrating violence. Clinical implications are discussed.